From Here to There: Mapping the Metropolitan Politics of Policy Mobilities. - Zimmermann, Karsten (Springer, 2020)
This chapter investigates the mechanisms and channels of movements of governance elements between metropolitan regions. It will do this by examining various professional networks, and policy and expert communities. The aim is to investigate to what extent cities and regions which are members of these policy networks and communities have actively facilitated the transfer of procedural and institutional elements of metropolitan planning and governance to/from metropolitan regions. Besides focusing on the mechanisms and channels, the rationale and interests of those policymakers and planning professionals involved are of primary importance. As such, this chapter explores the challenges, limits and opportunities of the mutation and transfer of such elements of metropolitan planning and governance. It will also reveal knowledge about which policies and ideas travel -or not- and why.
Keywords: Metropolregion; Regional Governance; Transfer; Städtenetz; Governance; Konvergenz; Planungsansatz; Internationale Zusammenarbeit; Regionalpolitik; Politiktransfer